1993
DOI: 10.1162/neco.1993.5.5.665
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Local Connectivity in the Neocortex

Abstract: Dual intracellular recording of nearby pairs of pyramidal cells in slices of rat visual cortex has shown that there are significant differences in functional connectivity between the superficial and deep layers (Mason et al. 1991; Nicoll and Blakemore 1993). For pairs of cells no farther than 300 μm apart, synaptic connections between layer 2/3 pyramidal neurons were individually weaker (median peak amplitude, A, of single-fiber excitatory postsynaptic potentials, EPSPs, = 0.4 mV) but more frequent (connection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 31 publications
4
18
0
Order By: Relevance
“…Thus, 70% of the synapses should be local. This is just within the order of magnitude that has been reported in other studies for local cortical connections (Gruner et al 1974;Nicoll and Blakemore 1993). In other words, there is indeed evidence that the approach of this study estimates real synaptic connectivity to a good approximation.…”
Section: The Technical Approachsupporting
confidence: 86%
“…Thus, 70% of the synapses should be local. This is just within the order of magnitude that has been reported in other studies for local cortical connections (Gruner et al 1974;Nicoll and Blakemore 1993). In other words, there is indeed evidence that the approach of this study estimates real synaptic connectivity to a good approximation.…”
Section: The Technical Approachsupporting
confidence: 86%
“…In addition, the activation peaks identified in the present study are within a few millimeters to those found in neuroimaging studies for verb generation (Warburton et al, 1996), semantic decision (Müller et al, submitted), and syntactic comprehension (Caplan et al, 2000). Even though currently available neuroimaging techniques do not provide sufficient spatial resolution to determine whether shared neuronal assemblies are involved in linguistic and nonlinguistic processing, the spatial vicinity and the known density of local cortical connectivity (Nicoll & Blakemore, 1993) make it likely that such findings reflect participation of overlapping neural tissue of association cortex in multiple functional domains subserved by multiple sensorimotor modalities.…”
Section: Discussionsupporting
confidence: 62%
“…Given current knowledge of the microcircuitry of the primary visual cortex (see Douglas et al, 1989;Douglas and Martin, 1991;Nicoll and Blakemore, 1993) it seems likely that intracortical inhibitory connections, mainly within cortical layers 2/3, form the substrate for interocular suppression in strabismus, which is then fed down to infragranular layers. However, there is also the possibility that suppressive effects observed in area 17 are partly due to feedback inhibition from extrastriate visual cortical areas, especially when the latencies of onset of suppression are unusually long (see Fig.…”
Section: Site and Nature Of Interocular Suppressionmentioning
confidence: 99%
“…Since the majority of excitatory synapses on neurons in area 17 derive from closely neighboring cells rather than from thalamic afferents (Kisvarday et al, 1986;Douglas and Martin, 1991) the responsiveness of cortical neurons is likely to depend crucially on "amplification" performed by local excitatory circuitry within the same OD column (Douglas et al, 1989;Nicoll and Blakemore, 1993). The intrinsic excitatory circuitry mediating this local amplification may indeed be unaffected by squint (Lowe1 and Singer, 1992;KGnig et al, 1993).…”
Section: Site and Nature Of Interocular Suppressionmentioning
confidence: 99%